(untitled) (American Journal of Islam and Society, 1995)
Introduction The topic of the Islamic impact on western civilization has received a great deal of attention from various Muslim scholars, and some attention from western scholars. When discussing this topic, Muslims usually concentrate on providing a list of important scientific discoveries made by Muslims with the intent of proving that Muslims made the discoveries before the Europeans. For example: Ibn Sina’ (d. 1036) used an air thermometer and Ibn Yunus (c. 900) used a pendulum many centuries before Galileo, al Idrisi (c. 1000) discovered and mapped the sources of the Nile River nine hundred years before the Europeans, and al Zarkayl proved that the planetary orbits were elliptical-not circular-many centuries in advance of Copernicus. Whereas the historical authenticity of these claims cannot be questioned, such discussion does not shed much light on the Islamic impact on western civilization. It is entirely possible that even though the Europeans made the noted discoveries many centuries after the Muslims, they did so without having any knowledge of earlier Islamic works. Such is the case in the above-mentioned examples. Hence, the issue of the Islamic impact on the West cannot be discussed in this context. Due to the shortcoming of the typical method of discussing the issue at hand, this paper will adopt an alternative method: the history of ideas and intellectual traditions in the Muslim world and the West. An attempt will be made to identify broad trends and characteristics of the western and Islamic intellectual traditions in order to discover possible links. The primacy of reason, logic, and the scientific method are the defining characteristics of the western intellectual tradition from the Renaissance to the present. Prior to the Renaissance, Christian theology determined ...